Emended description and resurrection of Sciaphila tosaensis and S. megastyla (Triuridaceae) - Suetsugu, Kenji; Kinoshita, Akihiko; Hsu, Tian-Chuan (Phytotaxa, 2019)
This paper presents a re-evaluation of the taxonomic status of Sciaphila tosaensis and S. megastyla (Triuridaceae) distributed in Japan and Taiwan. Based on the detailed morphological data, we concluded that these two species should both be treated as distinct species rather than synonyms of S. secundiflora. Sciaphila tosaensis differs from S. secundiflora and S. megastyla in having very narrow male perianth segments and female perianth segments distinctly shorter than male perianth segments. Sciaphila megastyla differs from the other two species in having very conspicuous style and stigma that is ca. 1.5 times as long as ovary in the flowering stage. Furthermore, a lectotype is designated of S. megastyla because its holotype has been lost. Molecular data also showed that there is considerable genetic divergence between S. tosaensis and S. megastyla, supporting that the morphological differences are mirrored by their genetic distances.